A new performance indicator for acute myocardial infarction. Issue 4 (1st April 2001) - Norris, R M
Abstract : OBJECTIVE: To develop a performance indicator for acute myocardial infarction which would reliably measure success of treatment and which might provide an alternative to case fatality as an audited outcome. DESIGN: A two year audit of all cases of acute myocardial infarction and resuscitated cases of out of hospital cardiac arrest from coronary heart disease in patients under 75 years of age. Behaviour of patients in calling for help, performance of the ambulance services in treating out of hospital arrest, and of the hospitals in providing resuscitation and thrombolytic treatment are audited separately. SETTING: Four district general hospitals. AUDITED INTERVENTIONS: Resuscitation from cardiac arrest and thrombolytic treatment. MAIN OUTCOME MEASURES: Hospital case fatality and lives saved/1000 patients treated. RESULTS: Overall, the lives of 83/1000 patients were saved (95% confidence interval 70 to 96). Of these, 29 (35%) were saved by out of hospital resuscitation and 38 (46%) by in hospital resuscitation from cardiac arrest. It was estimated that 16 lives (19%) were saved by thrombolytic treatment. There were no significant differences in case fatality among the hospitals. CONCLUSIONS: Lives saved/1000 patients treated is an easily measurable index and assesses performance of the ambulance service as well as of the hospital. Because it is relatively insensitive to diagnostic definitions, it may provide a robust alternative to case fatality as a performance indicator.